Asian development outlook, 2000 - Asian Development Bank (Oxford Oxford University Press, 2000)
The Asian development outlook 2000 is the Asian Development Banks annual survey of economic developments in the Asian and Pacific region.This year the outlook analysis the social challenge facing developing Asia as its enter the new millennium and it reco
Special chapter As the century turns the social challenges in Asia
Keywords: Economic development; Economics